THE ROLE OF CEPHALOSPORINS IN URINARY TRACT INFECTIONS TREATMENT IN CHILDREN - I. L. Chashchina; V. K. Tatochenko; M. D. Bakradze (Вопросы современной педиатрии, 2012)
The problem of effective diagnosis and treatment of acute urinary tract infection (UTI) remains relevant in connection with a high prevalence of this nosology and the growth of antibiotic resistance. The need to use of antibiotics in the treatment of acute UTI in children has no doubt. At the same time there are different opinions on duration, and route of administration of the antibiotics. It is not always possible to achieve the desirable effect after a long courses of antibiotic therapy, and duration of fever as a clinical marker of inflammation, was not significantly different in the appointment of oral and parenteral antibiotics. The effectiveness of treatment of acute urinary tract infections in young children depends not on the way of administration but on the dose that ensures the achievement of the minimum inhibitory concentration of the drug. Drugs of choice in patients with acute UTI are: inhibitor-protected aminopenicillins and cephalosporins of II and III generation. However, in children with acute UTI who received antibiotic therapy previously, as well as in suspected obstructive uropathy, the most likely causative agent is toxin-producing E. coli, which has a high degree of resistance to aminopenicillins, including protected. Therefore, the drugs of choice in this category of children should be the antibiotics of the cephalosporin group II–III generation.